Same time next year [videorecording (DVD)] - Mulligan, Robert, 1925-2008; Burstyn, Ellen, 1932-; Alda, Alan, 1936- (Universal, 2004)
A chance meeting between an accountant and a housewife results in a 26-year affair where they meet only once a year.